Razor girl : a novel - Hiaasen, Carl (Alfred A. Knopf, 2016)
"When Lane Coolman's car is bashed from behind on the road to the Florida Keys, what appears to be an innocent accident is anything but (this is Hiaasen!). Behind the wheel of the offending car is Merry Mansfield--the eponymous Razor Girl--so named for her unique, eye-popping addition to what might be an otherwise unexciting scam. But, of course--this is Hiaasen!--the scam is only the very beginning of a situation that's going to spiral crazily out of control while gathering in some of the wildest characters Hiaasen has ever set loose on the page. There's the owner of Sedimental Journey--the company that steals sand from one beach to restore erosion on another ... Dominick "Big Noogie" Aeola, the NYC mafia capo with a taste for the pinkest of sands ... Zeto, the small-time hustler who gets electrocuted trying to charge a Tesla ... Nance Buck, native Wisconsinite who's nonetheless the star of the red neck reality TV show, "Bayou Brethren" ... a psycho who goes by the name of Blister and who's more Nance Buck than Buck could ever be ... the multimillionaire product liability lawyer who's getting dangerously--and deformingly--hooked on the very product he's litigating against ... and Andrew Yancy--formerly Detective Yancy, busted to Key West roach patrol after he beat up his then-lover's husband with a Dustbuster--who's convinced that if he can just solve one more murder on his own, he'll get his detective badge back. That the Razor Girl may be the key to his success in this deeply ill-considered endeavor will be as surprising to him as anything else he encounters along the way--including the nine-pound Gambian pouched rats getting very used to the good life in the Keys ..."--